Implementation of Policy on Licensing and Reporting Procedures for Gold Mining Activities in Southeast Minahasa - Kasenda, Henny T. A.; Mokat, Jetty E. H.; Wawointana, Thelma (Technium Social Sciences Journal, 2025)
This study aims to determine how the implementation of policies related to gold mining licensing in Southeast Minahasa Regency. The research method used is qualitative research method, with data collection techniques namely observation, in-depth interviews, and document studies. The results showed that the implementation of the gold mining licensing policy in Southeast Minahasa Regency has not run effectively. Complex licensing mechanisms and unclear waiting times have caused license applications to be delayed for years, resulting in uncertainty among the mining community and a lack of interest in applying for licenses. Multi-agency supervision has proven ineffective due to technical constraints and inadequate infrastructure, such as limited patrol cars for large areas and difficult road conditions in the rainy season. Although licensing regulations have been comprehensively regulated in Law No. 4/2009 on Mineral and Coal Mining, with the latest revision in Law No. 3/2020, implementation in the field is still hampered by various structural, technical, social and cultural obstacles. The positive impacts of gold mining activities include contributions to the livelihoods of the poor, local economic growth, the formation of social solidarity within mining communities, and the provision of significant alternative employment. However, negative impacts include environmental degradation, public health risks, social conflict and criminality, potential loss of local revenue, and weak law enforcement and good governance. The implementation of this policy highlights the need for reforms in licensing management and more effective oversight, as well as more holistic policy integration to optimize the economic benefits of mining while minimizing its negative impacts on communities and the environment.